Distribution of Upper Circumpolar Deep Water on the warming continental shelf of the West Antarctic Peninsula. Issue 7 (3rd July 2017) - Couto, Nicole; Martinson, Douglas G.; Kohut, Josh; Schofield, Oscar
Abstract: We use autonomous underwater vehicles to characterize the spatial distribution of Upper Circumpolar Deep Water (UCDW) on the continental shelf of the West Antarctic Peninsula (WAP) and present the first near‐synoptic measurements of mesoscale features (eddies) containing UCDW on the WAP. Thirty‐three subsurface eddies with widths on the order of 10 km were detected during four glider deployments. Each eddy contributed an average of 5.8 × 10 16 J to the subpycnocline waters, where a cross‐shelf heat flux of 1.37 × 10 19 J yr −1 is required to balance the diffusive loss of heat to overlying winter water and to the near‐coastal waters. Approximately two‐thirds of the heat coming onto the shelf diffuses across the pycnocline and one‐third diffuses to the coastal waters; long‐term warming of the subpycnocline waters is a small residual of this balance. Sixty percent of the profiles that contained UCDW were part of a coherent eddy. Between 20% and 53% of the lateral onshore heat flux to the WAP can be attributed to eddies entering Marguerite Trough, a feature in the southern part of the shelf which is known to be an important conduit for UCDW. A northern trough is identified as additional important location for eddy intrusion. Key Points: Autonomous underwater vehicles provide measurements of mesoscale features (∼10 km) in the Antarctic with high‐spatial resolution Mesoscale eddy‐like features contribute significantly to the heat budget of the west Antarctic Peninsula continental shelf Upper Circumpolar Deep Water consistently intrudes onto the WAP shelf in bathymetric depressions